Analytical Approaches for Reinforced Concrete - Wu, Yufei (Woodhead Publishing series in civil and structural engineering., 2022)
Analytical Approaches for Reinforced Concrete presents mathematically-derived theories and equations for RC design and construction. The book applies deductive reasoning, logic and mathematics to RC. Laying out, deductively, the principles of RC, it encourages researchers to re-imagine and innovate using a solid conceptual framework. Sections consider the reasoning behind key theories, as well as problems that remain unsolved. The title presents key ideas in simple language and illustrates them clearly to help the reader grasp difficult concepts and develop a solid foundation, grounded in mathematics, for further study and research. The book is future-oriented, demonstrating theories that are applicable not only to conventional reinforced concrete members, but also to the envisaged structures of tomorrow. Such developments will increasingly require a deep, deductive understanding of RC. This title is the first of its kind, presenting a fresh analytical approach to reinforced concrete design and construction.